Speech activity circadian rhythm disturbance in children and adolescents with hypertension - V.M. Polyakov; L.V. Rychkova; N.A. Myasishchev; Zh.V. Prokhorova; I.A. Cherevikova; S.I. Kolesnikov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article is devoted to the study of the features of the dynamics of speech function (using associative activity as an example) in the circadian cycle of children and adolescents with hypertension (HTN). The research aims to distinguish between various approaches to teaching them. All participants were divided into the following two groups: the main group comprising 62 patients with HTN; the control group of 62 mostly healthy children. Both groups were matched for gender and age and then investigated by daily monitoring of blood pressure (BP) and multiple (threefold) neuropsychological testing following A.R. Luria's method in accordance with the conditional biorhythmological division of the day into three periods. Speech skills were assessed using C.G. Jung's associative experiment. In the participants with HTN, a comparative analysis of the dynamics of speech function in the circadian rhythm was carried out, and its results revealed a clear relationship between arterial pressure rhythm disturbances and speech activity. It was demonstrated that either an insufficient or significant decrease in blood pressure is commonly accompanied by a disruption of the circadian rhythm of speech activity. The observed daily fluctuations in the speech activity of the participants with HTN indicated desynchronosis and the formation of an altered biorhythm type, which is inverted with respect to the normal circadian rhythm of speech. In the participants with HTN, there was a change in the daily profiles of speech activity (associative processes), with the formation of a pathological circadian rhythm and the deterioration of speech activity.